Effect of Allium sativum and Nigella sativa on alleviating aluminum toxicity state in the albino rats - Abdel Ghfar, Sayed Soliman; Ali, Montaser Elsayed; Momenah, Maha Abdullah; Al-Saeed, Fatimah A.; Al-Doaiss, Amin A.; Mostafa, Yasser Sabry; Ahmed, Ahmed Ezzat; Abdelrahman, Mohamed (Frontiers in Veterinary Science, 2022)
The study objective was to evaluate the potential of Allium sativum, Nigella Sativa and their combination to reduce aluminum toxicity and return to the normal state. To attain these objectives, a hundred albino rats were randomly divided into five equal groups; the 1st group was used as a control group; the other four groups were exposed to aluminum 1600ppm in the water; the 2nd group was considered one of the four; the 3rd and 4th groups treated with Allium sativum 5% and Nigella sativa 5%, respectively; the 5th group treated with mix of Allium sativum 2.5% and Nigella sativa 2.5% for 8th weeks. After the 8th week, the aluminum treatment was stopped, and the second group, which was exposed to aluminum only, was divided into three groups. the 1st group was control group (was continued from the first experiment); the 2nd and 3rd groups treated with Allium sativum 5% and Nigella sativa 5%, respectively; the 4th group treated with mix of Allium sativum 2.5 % and Nigella sativa. Histopathological changes in the liver, kidney and testes were investigated after 8 and 16 weeks, and blood samples were collected after 4, 8 and 16 weeks for blood biochemical parameter. The results showed that the histopathological examination of liver, kidney and testes established congestion in blood vessels during aluminum exposure. Meanwhile, the treatment with Allium sativum or nigella or the mixture between them had positive effects on evading the harmful effects of aluminum in liver, Kidney and testes tissues. In addition, there were protective effects for Allium sativum and Nigella Sativa against aluminum on serum Creatininee, urea, ALT and AST concentrations. The present study concluded that supplementation with Allium sativum or Nigella sativa or their combination could reduce aluminum toxicity and return of the liver, kidney and testes to the normal state.